Prospect Analysis of Paleocene Coalbed Methane: A Case Study of Hangu Formation, Trans-Indus Ranges, Pakistan - Hamza Azam Qadri; Ali Wahid; Numair Ahmed Siddiqui; Syed Haroon Ali; Ahmed Abd El Aal; Amirul Qhalis Bin Abu Rashid; Mohd Najib Bin Temizi (Geofluids)
The methane trapped in the coal seams has emerged as an unconventional clean energy resource worldwide in this century. The proximate composition, ultimate content, cleat structure, porosity type, and pore structures are the debatable components for its trapping mechanism. Further, the brittle and ductile properties of minerals influence in the extraction of the methane from the coal seams. In this research, Coalbed methane prospect is demonstrated by analysing the Hangu Formation’s coal seam of Trans-Indus Ranges, Pakistan. This case study is helpful to find the occurrence, trapping ability, and methane extraction capacity in its cleat structures and pores. A number of samples were tested from the different coal mines in terms of these debatable components. The results indicate that the rank of studied coal is bituminous to subbituminous in which the carbon ratio, volatile matter, and sulfur contents are increasing with depth towards the south. The transitional connected face and butt cleats are partially filled with minerals and the intergranular, dissolved, and tissue pore types are also identified in it. It can be helpful for the occurrence, migration, and trapping of methane. Furthermore, the higher surface areas and cumulative pore volumes enhance the capacity of gas adsorption with depth in the study area. Moreover, the increasing brittle minerals in the coal composition towards the south can be helpful for the fracking of coal seams for economical gas extraction. It is suggested that this workflow can be implemented in any region with same coal rank and cleat types.